If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + 7) + -4(X + -2) = 3(X + 4) + -2 Reorder the terms: 3(7 + 4x) + -4(X + -2) = 3(X + 4) + -2 (7 * 3 + 4x * 3) + -4(X + -2) = 3(X + 4) + -2 (21 + 12x) + -4(X + -2) = 3(X + 4) + -2 Reorder the terms: 21 + 12x + -4(-2 + X) = 3(X + 4) + -2 21 + 12x + (-2 * -4 + X * -4) = 3(X + 4) + -2 21 + 12x + (8 + -4X) = 3(X + 4) + -2 Reorder the terms: 21 + 8 + -4X + 12x = 3(X + 4) + -2 Combine like terms: 21 + 8 = 29 29 + -4X + 12x = 3(X + 4) + -2 Reorder the terms: 29 + -4X + 12x = 3(4 + X) + -2 29 + -4X + 12x = (4 * 3 + X * 3) + -2 29 + -4X + 12x = (12 + 3X) + -2 Reorder the terms: 29 + -4X + 12x = 12 + -2 + 3X Combine like terms: 12 + -2 = 10 29 + -4X + 12x = 10 + 3X Solving 29 + -4X + 12x = 10 + 3X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-3X' to each side of the equation. 29 + -4X + -3X + 12x = 10 + 3X + -3X Combine like terms: -4X + -3X = -7X 29 + -7X + 12x = 10 + 3X + -3X Combine like terms: 3X + -3X = 0 29 + -7X + 12x = 10 + 0 29 + -7X + 12x = 10 Add '-29' to each side of the equation. 29 + -7X + -29 + 12x = 10 + -29 Reorder the terms: 29 + -29 + -7X + 12x = 10 + -29 Combine like terms: 29 + -29 = 0 0 + -7X + 12x = 10 + -29 -7X + 12x = 10 + -29 Combine like terms: 10 + -29 = -19 -7X + 12x = -19 Add '-12x' to each side of the equation. -7X + 12x + -12x = -19 + -12x Combine like terms: 12x + -12x = 0 -7X + 0 = -19 + -12x -7X = -19 + -12x Divide each side by '-7'. X = 2.714285714 + 1.714285714x Simplifying X = 2.714285714 + 1.714285714x
| (3x)/2-(12-x)/5=(7x+1)/3 | | -14=t+16 | | 1/3z=-11 | | 3x+12/6 | | 630+-90=x | | 48+-40=x | | 5((x-8)/5)-8 | | 2x^2-29x-31=0 | | 5k^2-15k-140=0 | | 1/5(x-1)+1/7(x+2)=1/35(x+8) | | 3x^3-x^2-10=0 | | 7m^2-6m-30=0 | | 81-v^2= | | x-0.18x=35000 | | x^2+32x-22=0 | | (-a-5b+6)3ab= | | 2(4y-9)=5(y-4) | | 2x^4-3x^3+5x^2+5x-7=0 | | 1/(x+9)^2 | | 32/4(8) | | .10x+.25y=7.45 | | 2x+6=7x-2 | | 2(5x+4)=2(3m-10) | | 1/2q-1=6 | | 38-4x=5x+16 | | 7/8x+1/2=7/8 | | 34x+5=10 | | (6x+7/6)+(3/2)=-2x/7 | | -4-2x=12-8x | | x^4-18x^3+81x^2=0 | | 3(x+4)-4(x-3)= | | (6x+7/6)+(3/2)=-2 |